ICKX, Johan (2021), Os Judeus de Pio XII, Vogais. ISBN 978-989-564-721-7, 459 pp. - Sequeira, Carla (História: revista da Faculdade de Letras da Universidade do Porto, 2023)
Recensão de ICKX, Johan (2021), Os Judeus de Pio XII, Vogais. ISBN 978-989-564-721-7, 459 pp.